Regional perspectives on Neolithic pit deposition : beyond the mundane - Anderson-Whymark, Hugo; Thomas, Julian (Neolithic Studies Group seminar papers, 2012)
The rise to prominence of pits within narratives of the British and Irish Neolithic is well-documented in recent literature. Pits have been cropping up in excavations for centuries, resulting in a very broad spectrum of interpretations but three main factors have led to the recent change in our perception and representation of these features: a broad shift in people's expectations as to what a Neolithic settlement should be; the development of the concept of 'structured deposition', within which pits have played a key role; and a dramatic rise in the number of pits actually known about. Develo.